Pendidikan Kesehatan Reproduksi untuk Meningkatkan Pengetahuan dan Mencegah Perilaku Seks Berisiko pada Remaja - Nurmisih Nurmisih; Ry Eny Mian Marisi Simanjuntak; Verawati Pulungan (Jurnal Abdimas Kesehatan (JAK), 2026)
The WHO indicates that the incidence of teenage pregnancy in women aged 15 to 19 years is 49 per 1,000 women. The incidence of teenage pregnancy in Indonesia is 48 per 1,000 women. According to the 2017 Indonesian Child Protection Agency (SDKI), the percentage of first-time sexual intercourse in adolescents increased from 59% in the 2012 SDKI to 74%. One of the problems that occurs during adolescence is risky sexual behavior. This problem tends to be carried out by adolescents aged 15-21 years. The results of the initial evaluation obtained an average knowledge score of 9.92 with a minimum score of 3 and a maximum of 14, the posttest showed an increase in knowledge score from 12.46 with a minimum score of 4 and a maximum of 15. Education using animated video media has been proven effective in increasing adolescent knowledge about reproductive health.